Detection Of Subsurface Geological Features Using Selected Geophysical Techniques - Arisona, Arisona (2018)
This study aimed (i) to simulate synthetic model using selected geophysical techniques buried subsurface, (ii) to characterize the subsurface geological features based on field data and (iii) to validate the measured physical parameter using statistical analysis.